Problematic Internet Pornography Use and Psychological Distress among Emerging Adults in Malaysia: Gender as a Moderator - Tan, Soon Aun; Goh, Yee Shan; Norzarina, Mohd Zaharim; Gan, Su Wan; Yap, Chin Choo *; Sarvarubini, Nainee; Lee, Ling Khai (MDPI, 2022)
Internet pornography use (IPU) refers to Internet-based sexually explicit materials that are ultimately used to elicit sexual feelings or thoughts. The accessibility of Internet pornography could lead to excessive exposure to pornographic messages, posing a risk to heavy users’ psychological health. This paper offers a preliminary understanding of the relationship between Internet pornography use and psychological distress among emerging adults and the moderating role of gender in the association. This cross-sectional study has taken a purposive sampling approach to recruit 144 emerging adult pornography users via the online survey method. The results indicated that males reported having more problematic Internet pornography use, and there were no gender differences in psychological distress. Meanwhile, gender is a significant moderator between Internet pornography use and psychological distress. The females were found to be more psychologically affected by their problematic Internet pornography use than the males. Overall, this study has provided a novel finding of the moderating role of gender in problematic Internet pornography use and psychological distress in the Malaysian context. This study also calls for a gender-focused sexual health programme for Malaysian emerging adults. Furthermore, the scores of problematic IPU in this study raise a concern over the effectiveness of current sex education in Malaysia. The scores may highlight the need to provide education targeting Internet pornography use.